The Dimension of Hydric Resources Quality in the Construction of the Sustainability Barometer (Revista Brasileira Multidisciplinar, 2013)
The Sustainability Indicators are parameters that characterize past events, evidence situational portraits of the present and assist in projecting future scenarios in relation to sustainability. These instruments allow periodic checks of the process of sustainable development at various scales. The Barometer of Sustainability fits this proposal, because, treating men and nature equally, it assesses the degree of sustainability and has been used from local to national scope. Within this perspective, the basic aim of this research was to analyze the quality dimension of water resources in the development of this instrument, taking as an example the city of Ribeirão Preto, SP, Brazil. The adopted methodology had as its main foundation the Seven Stages Cycle for implementing the Barometer of Sustainability. The Barometer of Sustainability as an assessment tool has proved to be useful in contributing to the understanding of natural phenomena, being relevant to the analysis of water resources at the local level. This tool is a component part of an environmental management process and cannot be considered alone. The Barometer of Sustainability showed that Ribeirão Preto is at a reasonable level in relation to the water resources which were analyzed and considered in the research. The index of the theme Water, originated from the assessment tool, showed the highest value among the other topics discussed in the Ecological Subsystem for the city, being in health and environmental compliance.
Keywords: Sustainability indicator; Water resources; Sustainability Barometer.